PERTUMBUHAN DAN HASIL JAGUNG MUDA (Baby Corn) PADA PERBEDAAN DOSIS KASCING (Growth and Yield of Baby Corn at Different Doses of Vermicompost ) - . Buhaira; Elly Indraswari (Bioplantae, 2013)
The study aims to evaluate the effect of vermicompost doses on baby corn growth and yield. This experimentwere carried out in randomized block design (RBD) with 5 replicates. Each experiment included 5 treatments 0.0 tons ha-1, 6.0 ton ha-1, 12.0 ton ha-1, 18.0 ton ha-1, and 24.0 ton ha-1. During of study, were measured some of vegetative and reproductive characteristic such as shoot dry weight, number of cobs per plant, cob length, cob diameter and yield. Observational data were statistically analyzed with ANOVA followed Duncan's multiple range test (DNMRT). The results showed that there were significant differences between vermicompost doses and most of characteristics such as shoot dry weight, number of cobs, cob length, cob diameter and the baby corn yield. The highest baby corn yield was achived at dose 18 tons of vermicompost per hectare. Key words : cobs, baby, corn, vermicompost.